2014
DOI: 10.1890/es14-00013.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic wasting disease model of genetic selection favoring prolonged survival in Rocky Mountain elk (Cervus elaphus)

Abstract: Abstract. As the area where chronic wasting disease (CWD) has been found continues to expand, there is concern over the impact it may have on elk (Cervus elaphus) populations that congregate on winter feedgrounds in Wyoming. A stochastic simulation model was created to determine the effect that genotype-specific CWD mortality rates had on a hypothetical free-ranging elk population. Life table data gathered from captive elk held in a CWD-contaminated facility was used to parameterize the model. Modeling the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…This line of inquiry is particularly relevant now with the spread of chronic wasting disease (CWD), a spongiform encephalopathy that affects cervids, causing global concern (Galloway et al., ; Mysterud & Rolandsen, ). It has been suggested that selection for prion disease resistance may play an important role in the long‐term dynamics of infected populations as CWD continues to spread (Monello et al., ; Robinson et al., ; Williams et al., ). Similarly, the magnitude of the effect of brucellosis on elk fitness should drive selection for increased resistance or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This line of inquiry is particularly relevant now with the spread of chronic wasting disease (CWD), a spongiform encephalopathy that affects cervids, causing global concern (Galloway et al., ; Mysterud & Rolandsen, ). It has been suggested that selection for prion disease resistance may play an important role in the long‐term dynamics of infected populations as CWD continues to spread (Monello et al., ; Robinson et al., ; Williams et al., ). Similarly, the magnitude of the effect of brucellosis on elk fitness should drive selection for increased resistance or tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This selective process, however, is slow because of the chronic nature of CWD mortality. Williams et al (2014) modelled the outcomes of a selective process on elk at the scale of decades to 100 years. The role that PrP genotypes play in shaping the population trajectories of CWD-infected cervid herds will likely be modified by hunting, which generally targets individuals in the oldest age class, of a specific sex (i.e.…”
Section: Strategies To Control the Spread Of Cwdmentioning
confidence: 99%
“…Although there is some evidence that these cervid PrP polymorphs reflect natural selection in CWD host populations (Robinson et al 2012), it is not known if their frequency has increased within CWD-infected areas in response to selection. Even with high levels of CWD exposure, the effects of selection on cervid PrP genotype frequencies could take decades [133], maybe even centuries [134] to manifest. Further, selection may not elicit a strong genotype shift in cervids because PrP genotypes do not confer complete resistance, but merely extend CWD incubation period [135], and susceptible animals would therefore have opportunities to reproduce before infection or during clinical progression [136].…”
Section: Selection Acts On Prion Genes and Prion Variantsmentioning
confidence: 99%